Histopathological Changes in The Gills of Cyprinus Carpio Infested With Ectoparasites - Wulandari, R D; Amalia, S R; Sari, P D W; Subekti, S (IOP conference series. Earth and environmental science, 2024)
This study aims to determine the histopathological changes in koi fish gills based on the degree of ectoparasitic infestation. The study found several categories of ectoparasite infestation, namely normal, mild, moderate, heavy and very heavy. In the gills with mild category, there were histopathological changes in hyperplasia, in the gills with moderate infestation category, hyperplasia and fusion occurred, in the heavy category infestation there were hyperplasia and telangiectasia, and in the category of very heavy infestation, there were hyperplasia. fusion, telangiectasia and vacuoles. The histopathological scoring value on the gills with the categories of mild, moderate, severe infestation degrees is the mild category, while the gills with the category of very heavy infestation degrees is the heavy category. Correlation test of the degree of infestation and scoring of histopathological changes obtained a ρ value of 0.832. It can be concluded that the increase of ectoparasite infestetation will be followed by the increase of tissue damage level.